Enhancing the contribution of small and medium-sized enterprises to local economic development in Oshakati Town, Namibia - Kakwambi, J. N. N. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--Stellenbosch University, 2012.